Development of Purpureocillium lilacinum ZJPL08 wettable powder and its toxicity to Diaphorina citri Kuwayama - DU Danchao; ZHU Li; PU Zhanxu; LIU Shunmin; CHEN Guoqing; LU Lianming (浙江大学学报. 农业与生命科学版)
The fungus Purpureocillium lilacinum ZJPL08 presents strong pathogenicity against citrus psylla (Diaphorina citri Kuwayama), so the development of a biocontrol agent based on this fungus is of great significance for the prevention and control of D. citri. In this study, P. lilacinum ZJPL08 was used as the active ingredient to screen carriers, wetting agents, and ultraviolet (UV) protectants. The results showed that the optimum formulation for P. lilacinum ZJPL08 wettable powder (WP) was as follows: 10.00% conidial spore powder of ZJPL08 (active ingredient), 3.00% sodium dodecyl sulfate (wetting agent), 5.00% sodium lignosulfonate (dispersant), 0.25% humic acid (UV protectant), 0.10% CaCl2 (promoter of spore germination), 0.05% xanthan gum (adhesive), and 81.60% diatomite (carrier). Under these conditions, the P. lilacinum ZJPL08 WP achieved a spore concentration of 3.25×1010 spores/g, a suspension rate of 85.67%, a wetting time of 86.22 s, a fineness of 95.39% powder passing through a 300 mesh sieve and a pH value of 6.65; all the indexes met the requirements of national pesticide formulation products. The semi-field control efficiency test results showed that the 1 500-fold dilution of P. lilacinum ZJPL08 WP could effectively control D. citri, with a control efficiency of 97.78%, which was not significantly different from the 1 000-fold dilution of the control insecticide, 30% thiamethoxam WP (100% control efficiency), but was significantly greater than the 1 500-fold dilution of 1.80% avemectin emulsion (78.33% control efficiency). In conclusion, the P. lilacinum ZJPL08 WP developed in this study presented excellent control efficiency for D. citri, which probably has important application prospects in replacing chemical pesticides.